Task-Technology Fit for Textile Cyberpreneur’s Intention to Adopt Cloud-based M-Retail Application - Nik Zulkarnaen Khidzir; Wan Safra Diyana; Tan Tse Guan; Mohammad Ismail (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Task-Technology  Fit  (TTF)  model  has been widely used in many researches for understanding the compatibility of task characteristics and technology characteristics. Applying TTF in mobile retail (m-retail) context from the perspectives of retailers might give the insights of their intention to adopt mobile cloud application technology for online business operations. Since it is currently common for retailers such as textile cyberpreneurs to conduct m-retail via the uses of certain mobile applications and devices, it is essential to investigate the usage intention based on task-related factors. Therefore, the objective of this study is to examine the compatibility of textile cyberpreneurs’ tasks and characteristics of cloud-based m-retail application (CBMA) along with their usage intention to adopt the technology for their online business transactions. This research model surveyed 348 Malaysian textile cyberpreneurs. The results show that both task characteristics and technology characteristics have positive significant effects on task-technology fit. Further analysis also suggests the fitness between task and technology has positively influenced textile cyberpreneurs’ intention to adopt cloud-based m-retail application. The findings contributed in acknowledging the usage intention among textile cyberpreneurs based on task-related factors which might be useful for service providers in delivering the right services for end-users. The directions for future research are also discussed.